2011
DOI: 10.1038/tpj.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate consolidation treatment according to pharmacogenetics of MTHFR ameliorates event-free survival in childhood acute lymphoblastic leukaemia

Abstract: Recent advances in treatment for childhood acute lymphoblastic leukaemia (ALL) have significantly increased outcome. High-dose methotrexate (MTX) is the most commonly used regimen during the consolidation period, but the optimal dose remains to be defined. We investigated the usefulness of the MTHFR genotype to increase the MTX dosage in the consolidation phase in 141 childhood ALL patients enrolled in the ALL/SHOP-2005 protocol. We also investigated the pharmacogenetic role of polymorphisms in genes involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 25 publications
0
47
4
2
Order By: Relevance
“…Polymorphisms in genes for these proteins as well as proteins related to folate physiology have all been postulated to modulate MTX-related hematologic toxicity. Additionally, polymorphisms in ATP binding casette genes such as ABCB1 and ABCC2, which encode other proteins involved in MTX transport, have been implicated in higher incidence of myelosuppression during MTX treatment [16][17][18][19]. The MTHFR C677T allele has been the most widely studied pharmacogenetic factor in MTX toxicity.…”
Section: Hematologic Toxicitymentioning
confidence: 99%
“…Polymorphisms in genes for these proteins as well as proteins related to folate physiology have all been postulated to modulate MTX-related hematologic toxicity. Additionally, polymorphisms in ATP binding casette genes such as ABCB1 and ABCC2, which encode other proteins involved in MTX transport, have been implicated in higher incidence of myelosuppression during MTX treatment [16][17][18][19]. The MTHFR C677T allele has been the most widely studied pharmacogenetic factor in MTX toxicity.…”
Section: Hematologic Toxicitymentioning
confidence: 99%
“…An earlier similar study showed patients with the MTHFR 677CC genotype had a trend of longer TTP (but not response) to cisplatin/gemcitabine in Stage IV NSCLC (Alberola et al, 2004). Other recent reports showed that acute lymphoblastic leukaemia (ALL) patients with 677TT genotype had a significantly higher incidence of relapse compared to other genotypes after the consolidation methotrexate therapy (D′Angelo et al, 2011;Salazar et al, 2011). However, other studies showed MTHFR 677T allele carriers had a higher response rate to 5-FU-based chemotherapy (Cohen et al, 2003;Fernández-Peralta et al, 2010) or FOLFOX therapy (Etienne-Grimaldi et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In Mexican and SI patients with ALL, -317 GG genotype was found to be involved in the relapse and lower overall survival [19,27]. DHFR variants were found to have no influence on the response to methotrexate in the Spanish population, but the DHFR-680C>A variant was found to be associated with neutropenia [49]. Discordant results of DHFR variants could be majorly due to the difference in the distribution of DHFR variant alleles.…”
Section: Clinical Relevance Of Studied Dhfr Variantsmentioning
confidence: 99%